Viver em infoestimulação: por uma poética contemporânea - Rosa, Raul Dotto (2023)
In this research in Visual Poetics, it is proposed to think about technological infostimulation in the modeling of the “self”, generating self-images from personal experiences with devices connected to the internet. In the elaboration of the works, it is intended to reflect on potential transformations in the perception and projection of the self, through computational and three-dimensional images, suggested in fictional structures, through practical procedures and theoretical reflection, based on studies in the areas of Cognitive Sciences and of Philosophy. The methodology is guided by poetic operations, in which we sought to observe, select, study, manipulate, experience and know the uniqueness of the research object, completing the critical review of each work, resulting in the creation of photographs, drawings, videos, sculptures and installations. The importance of the research is justified, due to the increasing use of information technologies connected to the Internet in daily activities. At the end of the research, with the writing of the thesis, it is expected to contribute through poetics with the thought about the possible implications of infostimulation in the construction of the “self” and its relationship with the world, in the context of Contemporary Art.